ECOLOGICALLY SAFE GROWING TECHNOLOGIES FOR SPRING BARLEY ON ORGANIC FARMING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Field trials were carried out on organic farming fields at the Research Institute of Agriculture of the Latvia University of Agriculture (LUA). The content of nitrates in soil, the influence of previous plants (red clover, winter rue, bare fallow, fallow and green manure), use of stable manure (60 t ha-1 or without) and harrowing (without harrowing, before shooting, at the stage of clustering, before shooting and at the stage of clustering) on the yield and weediness of spring barley „Sencis” were tested during 2003-2004. The content of nitrates in soil was 8-79 mg kg-1. Previous plants and stable manure influenced barley grain yields. Harrowing increased the yields of barley only after winter rye for green manure by using stable manure, but the time of harrowing had no influence on the yield of barley. The quality of grain was satisfactory. 1000 thousand weight was medium – 33.5–38.4 g, medium was also volume weight – 609.0–633.5 g. The content of total protein was satisfactory to good – 9.6 – 11.7 %.